Edukasi dan Penerapan 3R dalam Pengelolaan Sampah di Dusun Balinappang Kecamatan Pallangga untuk Kesadaran Lingkungan Berkelanjutan - Abd.Gafur; Nurgahayu; Nurul Fadilah; Alifia Vitaloka Camila; Nahdah Aqilah Mansur; Arifah Ihratul Magfirah; Fairuz Muhammad Hilmi Muzhaffar (Compromise Journal Community Proffesional Service Journal, 2025)
Waste management remains a significant challenge in Dusun Balinappang, Desa Bontoramba, Kecamatan Pallangga, Kabupaten Gowa, Makassar City. Low community awareness regarding waste sorting and proper management has led to a decline in environmental health quality. Improper waste management can result in various environmental problems, such as water, soil, and air pollution. To address this issue, a community service activity was conducted with the aim of improving public knowledge and awareness on proper waste management through the 3R approach (Reduce, Reuse, Recycle). The method used for this activity involved education through the use of posters. The posters were designed to be visually engaging and simple, making them easy for the community to understand. This visual medium effectively conveyed information about the importance of waste sorting and applying the 3R principles. Additionally, pre-tests and post-tests were used as evaluations to measure the change in participants’ knowledge before and after receiving the education. The pre-test was conducted to assess participants' initial understanding, while the post-test helped determine the extent of their knowledge improvement regarding 3R concepts and waste management practices. The results of the activity showed a significant increase in the community’s understanding of 3R principles and proper waste management techniques. The community began to demonstrate positive behavior changes, such as sorting household waste more carefully and reusing materials that could be recycled. This shift contributed positively to raising environmental awareness and improving the health of the local community. With this simple yet effective education, it is hoped that the program can continue and be expanded to other areas. This initiative will contribute to creating a cleaner, healthier, and more sustainable environment, which will have a long-term positive impact on the quality of life for the community.